Beyond traditional teaching: impact of web-based instructional application on Lagos State secondary school students’ academic achievement and attitude in commerce - Usman, Mariam Omosalewa; Akindoju, Olugbenga Gabriel; Abanum, Collins Ifeanyichukwu; Ariyibi, Olanrewaju Olasupo; Ogungbo, Moruf Olawale (African Perspectives of Research in Teaching and Learning Journal, 2024)
This study examined the difference in the achievement and attitude of the commerce-taught students using WBIA and those traditionally taught at Lagos State Secondary School. Researchers have often focused on problems related to the field of science, neglecting the other arms at this level. A research question and a hypothesis were formulated to guide this study. This research uses a mixed method (quantitative and qualitative). A convenience sampling technique was used to select two intact classes of 100-80 students drawn from the population of students who offer commerce in Lagos State Secondary Schools. A WBIA was developed to teach five different topics in commerce, a standardised commerce achievement test, and a web-based instructional application interview guide were used to collect data and validated. The reliability of the commerce achievement test was r = 0.83. The hypothesis formulated was analysed using MANCOVA. The result of the hypothesis signifies a statistically significant difference in achievement and shows a positive attitude towards commerce at [F (1,104) = 266.08; p < .05, attitude F (1,104) = 9.96; p < .05. The use of WBIA features that link commerce concepts with real-world scenarios is highly recommended.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 8, 2024
Keywords: Web-based instructional application (WBIA); Commerce; Academic Achievement; Student attitude; Senior secondary school; MANCOVA; Connectivism; Academic achievement; Web-based instructional application